Gerbera jamesonii المسبب لمرض تبقع اوراق نبات الجربراplanimi Pestalotiaتشخيص الفطر - شاكر, كونر عبد الوهاب (Al-Nahrain Journal of Science, 2012)
The study is aiming to isolate and diagnose the fungal causes of leaf spot disease on Gerbera jamesonii Adlam.plants by conducting field survey of some local nurseries in two locations in Baghdad, in the Palestine Street (Al-Khirat, Al-Zina) and Zaiyuna (Zainab, Zaiyuna, Baghdad) for the years 2007-2008.The infection percentage on Gerbera plants showed ranging between 10-40% and the existence of significant differences (P ≤ 0.05) between the nurseries. Outcome of the study of diagnostic and pathogenicity of the pathogen was found to be genus Pestalotia planimi Vize.on the contaminated plants with fungal pathogen, and this is the first record of the disease in Iraq.Keywords: conidiospore, leaf spot, Pestalotia planimi , Gerbera jamesonii,